Challenges of Transitioning to e-learning System with Learning Objects Capabilities - Raspopovic, Miroslava; Cvetanovic, Svetlana; Jankulovic, Aleksandar (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Higher education institutions that have implemented blended and/or online learning need to be on the forefront of the cutting edge technological and educational advances in order to remain competitive and innovative. This task is usually very difficult due to the budget constraints that many institutions have. Keeping up with the current technological advances often brings not only financial challenges, but also transitional challenges that may put at risk learning quality and reputation of the institution, as well as performance of students. This work describes the features of the system, and the results and challenges of transitioning to an e-learning system that displays learning materials through a sequence of reusable learning objects (LOs) from the system that does not have these capabilities. Based on the research of existing methodologies and the results of this research, this work proposes a methodology for transferring into an LO-oriented e-learning system. Findings of this work reveal advantages, disadvantages, and potential obstacles of e-learning system implementation with LOs and give an overview of suggestions for implementation improvements. These suggestions are given based on evaluation of the implementation of an LO-oriented e-learning system, after the transition from the traditional non-LO oriented e-learning system.